UPAYA PENINGKATAN KOMPETENSI ANGGOTA SATUAN POLISI PAMONG PRAJA (SATPOL PP) KABUPATEN TEMANGGUNG - Joko Nursusilo; Sulastiningsih Sulastiningsih (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study aims to improve the competence of members of the Civil Service Police unit in Temanggung Regency. The research was carried out starting in October 2022. This type of research is descriptive qualitative. Collection of interview and observation data. Interactive Model of Analysis. The results showed: 1) The competence of the members of the Civil Service Police Unit in Temanggung Regency was not optimal because: the educational background of Satpol PP members was low, socialization had not been able to make street vendors stop selling in prohibited places, some Satpol PP members were often carried away by emotions and the lack of budget for competency improvement 2) Efforts made to improve the competence of Satpol PP members: propose to BKPSDM to improve the competence of Satpol PP members, attend knowledge training which consists of analytical thinking, conceptual thinking and expertise, carry out controlling by observing locations, outreach and controlling actions , providing guidance to Satpol PP members so they can refrain from being easily carried away by emotions and submitting a budget to members of the Temanggung Regency DPRD